Systemic Treatments for Lichen Planopilaris and Frontal Fibrosing Alopecia: A Retrospective Study of 315 Patients - Mathias Willaert; Tristan van Dongen; Petra Dikrama; Tamar Nijsten; DirkJan Hijnen; Rick Waalboer-Spuij (Acta Dermato-Venereologica)
Lichen planopilaris and frontal fibrosing alopecia are common variants of primary lymphocytic cicatricial alopecia, leading to permanent hair loss. Despite widespread use of various systemic treatments, evidence-based guidelines for these conditions are lacking. This study investigates the effectiveness of systemic treatment options in patients with lichen planopilaris and frontal fibrosing alopecia through a retrospective cohort analysis. Medical records of patients treated at the Department of Dermatology between 2016 and 2022 at the Erasmus University Medical Center Rotterdam, the Netherlands were reviewed. Of 315 patients identified (161 lichen planopilaris and 154 frontal fibrosing alopecia), the majority were female (90.5%), with hydroxychloroquine being the most common systemic treatment, used by 65.2% of lichen planopilaris and 57.8% of frontal fibrosing alopecia patients. Methotrexate had the highest response rate for lichen planopilaris (79.2%), while retinoids showed the highest response for frontal fibrosing alopecia (73.9%). However, treatments with cyclosporine A and retinoids had higher discontinuation rates due to side effects. This study suggests methotrexate and cyclosporine A may be most effective for lichen planopilaris, and cyclosporine A and retinoids for frontal fibrosing alopecia, though side effects remain a concern. Limitations include the retrospective design and the absence of standardized outcomes. Prospective studies are recommended to validate these findings.